The Effect of Aerobic Fitness on Visuospatial Attention in Young Adults - (:unkn) unknown (My University, 2013)
The recently popular commercial brain- and visual-training programs have become a multimillion dollar industry with claims to enhance various cognitive functions. Although no empirical evidence directly supports the efficacy of these programs, sport expertise has been shown to influence cognition, lending indirect support for training efficacy. However, researchers investigating attention and sport expertise have not previously controlled for level of physical activity, which may also contribute to enhanced cognitive processes. Prior studies have shown strong correlations exist between physical fitness and cognition in both children and older adults. Yet, few studies have examined this relation in young adults, and no studies have examined the effect of aerobic fitness on cognition while controlling for sport participation and action video game playing habits. The purpose of this study was to determine the extent to which aerobic fitness relates to visuospatial attention performance in young adults while controlling other factors. A secondary purpose was to identify a potential physiological mechanism underlying the relation between exercise and cognition. Heart rate variability has been linked to both aerobic fitness and cognitive performance and was used in this study. Thirty-five healthy adults (ages 18-29) participated. Data collection included submaximal VO2max, BMI, motivation, sport involvement, performance on two visual attention tasks, and heart rate variability. BMI, motivation, and sport involvement did not significantly correlate with aerobic fitness and were excluded from further statistical analyses. Contrary to our hypothesis, performance on the attention tasks did not significantly correlate with aerobic fitness while controlling for sport participation (MOT: r = .120, p = .250; CVAT: r = .166, p = .174). Heart rate variability also did not significantly correlate with visual attention (SD: r = .064, p = .375; LF/HF: r = - .312, p = .057). The findings of this study did not support a relation between aerobic fitness and visual attention in young adults. The effect of chronic exercise on cognition may be more apparent in children and older adults who are still cognitively developing or experiencing age-related cognitive declines. To improve visual attention in young adults, more study is required to determine the efficacy of `brain' training.